2020
DOI: 10.1038/s41598-020-74435-9
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal synchronization of foodborne outbreaks in the United States, 1996–2017

Abstract: Modern food systems represent complex dynamic networks vulnerable to foodborne infectious outbreaks difficult to track and control. Seasonal co-occurrences (alignment of seasonal peaks) and synchronization (similarity of seasonal patterns) of infections are noted, yet rarely explored due to their complexity and methodological limitations. We proposed a systematic approach to evaluate the co-occurrence of seasonal peaks using a combination of L-moments, seasonality characteristics such as the timing (phase) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…In prior research, we found variations in seasonal peak timing across pathogens using harmonic regression modeling [ 33 , 34 , 35 ]. Such fluctuations could occur for a variety of social and environmental reasons [ 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In prior research, we found variations in seasonal peak timing across pathogens using harmonic regression modeling [ 33 , 34 , 35 ]. Such fluctuations could occur for a variety of social and environmental reasons [ 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study in Australia used surveillance data on Ross River virus and Barmah Forest virus to identify peak timing, as well as to estimate the impact of a false-positive Barmah Forest virus epidemic in 2013 [ 53 ]. We had recently demonstrated the summertime synchronization of foodborne outbreaks in the USA using the national surveillance data [ 54 ]. Thus, secondary data could be extremely useful as part of formative research, for extrapolating seasonal trends from smaller and context specific primary seasonality research, as well as for general forecasting and modeling.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive studies often reported linear fluctuations in mean and median incidence over time or the sum and percentage of infections by consecutive seasons or months (CID 1-11). Studies frequently estimated seasonal peak timing by identifying the calendar month or season with the highest sum, percentage or average incidence of infections (CID [12][13][14][15][16][17][18]. Study rationales aimed to understand trends in infection severity for creating, modifying or evaluating public health interventions.…”
Section: Describing Trends In Infections Over Timementioning
confidence: 99%
“…Precise estimation of peak timing helps identify differences in seasonal patterns by pathogen, subpopulation and geographic location [ 12 ]. Synchronisation of pathogens' peaks suggests possible co-infections and shared food/water- or environmental-drivers of infection [ 12 , 16 , 17 ]. Lags between peaks of infections and their drivers, best assessed with more granular temporal data, inform forecasts of peak incidence for early outbreak warnings [ 12 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%